Analisis Transmisi Kebijakan Moneter Syariah Terhadap Kinerja UMKM di Kota Serang - Syahlaa Salsabiil Putri; Nasywa Nabil Oktaviani; Ratu Eprilla Maharani; Rasidah Novita Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The branch of economics called Islamic monetary policy discusses the nature, function, and impact of monetary policy in a country. Not only the supply and demand of money, this Islamic monetary emphasizes the principles of justice and brotherhood that pursue equality and create equitable distribution of wealth and income. The purpose of this research is to see how the transmission of Islamic monetary policy on the performance of MSMEs in Serang City. To stay competitive or even win the competition, an organization can evaluate its strategy in the face of an ever-changing market. Micro, Small and Medium Enterprises (MSMEs) are very flexible and resilient to the economy, but they have several limitations such as financial capabilities and human resources. To gain a competitive advantage, MSMEs must be able to determine the right strategy. This research uses a descriptive approach by using observation techniques and interviews with MSME actors in Serang City. Based on the results of the study, it shows that the sharia monetary policy applied to the performance of MSMEs in Serang City is very helpful for business actors by providing access to safe capital, effective money management training, and information technology-based marketing training.